Relationship Between Teachers’ Instructional Practices And Students’ Performance In Social Studies In Colleges Of Education In North East, Nigeria - Isyaku, Suleiman; Olayinka, Shittu Lukman; Oti, Gladys O.; Ariya, Dauda A.; Ridwan, Muhammad (BIRCU, 2024)
This study investigated the relationship between teachers’ instructional practices and students’ performance in Social Studies in colleges of education, in North East, Nigeria. The study raised three objectives and answered three research questions. The descriptive survey and correlational research designs were adopted for the study. The population was made up of 5,735 Social Studies students and 39 Social Studies teachers in both federal and state colleges of Education in north-east geographical zone, Nigeria. systematic sampling technique was used to select sample for the study; the sample used was 16 social studies teachers and 351 students in the four colleges of education in north-east geographical zone, Nigeria. Two instruments were used which were social studies teachers instructional practices classroom observation checklist and Social Studies students performance result record. The validity of the three instruments was determined by five experts from Social Studies Education, Research, Measurement and Evaluation units from Faculty of Education, University of Jos. The reliability of the instruments was established using inter-rater methods of reliability which yielded reliability index of 0.874 for the teachers instructional practices classroom observation check list. The statistical tools used in answering research questions were mean and standard deviation. The findings revealed that that lecture, discussion, and questioning teaching methods are mostly used by teachers in social studies. The inquiry method, problem-solving method, simulation method, dramatization, construction method, presentation, and concept mapping are teaching methods that are rarely used by teachers in social studies. It revealed that there is a significant relationship between the teaching methods, instructional materials, teachers' questioning techniques, social studies teachers' lesson presentations, teachers’ evaluation techniques and students’ performance in social studies. It further indicated that students' performance relative to teachers' instructional practices in state and federal colleges of education is not the same.